Bihar Second Five-Year Plan Progress Report for the Period Ending June, 1958 - Planning Commission (Planning Commission, 1958)
Abstract of Expenditure Scheme wise Progress- Agricultural Production Minor Irrigation Soil Conservation Land Development Marketing Animal Husbandry Dairying and Milk Supply Forest.
Bihar